Penguatan Literasi Iklim Anak dan Remaja Melalui Edukasi Partisipatif Berbasis Kearifan Lokal di Kecamatan Pulau Ternate - Abbas, Sukardi; Syawal, Julkarnain; Sahjad, Sumarni; Umasugi, Nurain; Nurbaya, Nurbaya (Jurnal SOLMA, 2025)
Background: Climate change is a global threat that has a significant impact on human life, including vulnerable groups such as children and adolescents. Ternate City as an archipelago has a high vulnerability to climate disasters such as floods, landslides, and coastal abrasion. This service aims to improve climate literacy for children and adolescents through a participatory approach based on local wisdom. Methods: this community service activity uses the Community-Based Participatory Research (CBPR) method with data collection techniques in the form of observation, interviews, FGD, and Photovoice. Results: shows that this approach is effective in increasing participants' awareness and involvement in climate change issues. The program has also succeeded in forming an environmentally conscious community that can become agents of change at the local level. Conclusions: this activity provides a climate education model that can be replicated in other island regions in Indonesia.